TELADAN PENDERITAAN TUHAN YESUS BERDASARKAN MATIUS 27: 32-44 - Supriadi Oet (Sekolah Tinggi Teologi Arastamar Bengkulu, 2017)
Suffering is the part that follows human life. Suffering comes in different forms and is felt differently by each human being. Jesus Christ himself suffered. So believers need not be surprised if they experience suffering. But behind Jesus' suffering, there are important principles that we can emulate. Therefore through this writing, we try to provide an understanding of the example of suffering from the Lord Jesus.